Earthworms (Oligochaeta: Glossoscolecidae) of the Amazon region of Colombia - M., Alexander Feijoo; Celis, Liliana V. (Zootaxa, 2012)
The descriptions of three species of terrestrial oligochaetes, family Glossocolecidae, are added to the catalog of earth-worms of Colombia’s Amazon region: Martiodrilus (Maipure) huitoto sp. nov., M. (Cordilleroscolex) mirania sp. nov.,and Periscolex coreguaje sp. nov.). With these new registries, the earthworms fauna of Colombia now contains 136 spe-cies. A key is included to differentiate species of Periscolex, and several observations are given related to the distribution of species and the presence of earthworms depending on changes in land use.